2012
DOI: 10.3727/096368912x612512
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial Infusion of Autologous Bone Marrow Mononuclear Cells in Patients with Moderate to Severe Middle Cerebral Artery Acute Ischemic Stroke

Abstract: Transplantation of autologous bone marrow mononuclear cells (BMMCs) has been proven safe in animal and human studies. However, there are very few studies in stroke patients. In this study, intra-arterial autologous BMMCs were infused in patients with moderate to severe acute middle cerebral artery infarcts. The subjects of this study included 20 patients with early or late spontaneous recanalization but with persistent deficits, in whom treatment could be initiated between 3 and 7 days after stroke onset. Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(35 citation statements)
references
References 41 publications
4
31
0
Order By: Relevance
“…These results are consistent with the safe administration of BM-MNC in the acute (24-72 hours) treatment of strokes in adult population (Savitz et al, 2011). Intra-arterial administration of BM-MNC has also been performed in stroke patients with infusion into the middle cerebral artery (Friedrich et al, 2012;Moniche et al, 2012). Additional trials evaluating the safety of intra-arterial infusion of CD34+ cell populations and MSC have been completed (Banerjee et al, 2014;Bang et al, 2005).…”
Section: Does Route Matter?supporting
confidence: 82%
“…These results are consistent with the safe administration of BM-MNC in the acute (24-72 hours) treatment of strokes in adult population (Savitz et al, 2011). Intra-arterial administration of BM-MNC has also been performed in stroke patients with infusion into the middle cerebral artery (Friedrich et al, 2012;Moniche et al, 2012). Additional trials evaluating the safety of intra-arterial infusion of CD34+ cell populations and MSC have been completed (Banerjee et al, 2014;Bang et al, 2005).…”
Section: Does Route Matter?supporting
confidence: 82%
“…These results agreed with that of the previous work by Bhasin et al (18); however, they reported that the stem cell group showed more functional improvement, but they did not find significant difference in functional brain MRI between experimental and control groups at 8 weeks and 6 months post-treatment. Also, Friedrich et al (22) reported non-significant difference in infarct volumes or infarct densities between groups with and without clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of autologous bone marrow-derived MSCs in pilot studies has been proven safe in human patients with acute middle cerebral artery infarcts (Bang et al, 2005; Battistella et al, 2011; Savitz et al, 2011; Friedrich et al, 2012; Moniche et al, 2012; Banerjee et al, 2014). Moreover, improvements of neurological recovery were noted (Bang et al, 2005; Battistella et al, 2011; Savitz et al, 2011; Friedrich et al, 2012; Moniche et al, 2012; Banerjee et al, 2014). Unfortunately, these studies lacked appropriate control groups, which limits conclusions around the efficacy of cell therapy.…”
Section: Mesenchymal Stem Cells In Striatal and Neocortical Strokementioning
confidence: 99%